Reductions of Antarctic ozone due to synergistic interactions of chlorine and bromine - Mcelroy, M. B.; Salawitch, R. J.; Wofsy, S. C.; Logan, J. A. (1986)
The vertical column density of ozone observed in October over Antarctica has fallen precipitously over the past 10 yr. The concentration at Halley Bay (76 deg S, 27 deg W), expressed conventionally in Dobson units (DU), has dropped from about 300 DU in 1975 to less than 200 DU in 1984. Values in 1985 were even lower, comparable with the lowest values recorded anywhere on earth. It is suggested here that the loss of O3 in Antarctica may be attributed to catalysis of O3 recombination by a scheme in which the rate-limiting step is defined by the reaction of ClO + BrO - Cl + Br + O2. Concentrations of NO2 must be low and heterogeneous reactions involving particles in the polar stratospheric clouds must be an important element of the relevant chemistry. Industrial sources make important contributions to the contemporary budgets of both BrO and ClO and are likely to grow significantly in the future.